Robinson Crusoe - Defoe, Daniel (b, 2001)
During one of his several adventurous voyages in the 1600s, an Englishman becomes the sole survivor of a shipwreck and lives on a deserted island for more than twenty-eight years.
Keywords: Crusoe, Robinson (Fictitious character) -- Juvenile fiction; Shipwrecks -- Fiction; Survival -- Fiction